3D-data Runinskrifter på lösföremål från Sigtuna, Uppland 3D data Runic inscriptions on portable objects from Sigtuna, Uppland - Kitzler Åhfeldt, Laila (Swedish National Heritage Board, 2024)
Detta dataset innehåller 3D-modeller av runinskrifter på föremål från vikingatida och tidigmedeltida Sigtuna. Föremålen ingår i Sigtuna Museums samlingar.

This dataset includes 3D-scans of runic inscriptions on portable objects from Viking Age and Early Medieval Sigtuna, Uppland. The objects belong to the collections of Sigtuna Museum.

The signum U + code + number is an ID-code used in the record of runic inscriptions kept by Runverket at the Swedish National Heritage Board. The signum is used in most publications and web-based resources. It is the key to find further references on a specific runic inscription and the object carrying it.

Föremålen 3D-skannades 2010 med ATOS II SO (Small Objects), vid Arkeologiska Forskningslaboratoriet (AFL), Stocholms Universitet, av Laila Kitzler Åhfeldt och Joakim Schultzén.

Till U NOR2001:19 (Sl 97, syllabarium) användes mätvolym MV135 = 135x108x95mm, upplösning 0,1mm i slutresultatet.

Till övriga föremål användes mätvolym MV35= 35x28x14mm, upplösning 0,027mm i slutresultatet.
Keywords: rune; Runverket; runor; runinskrift; runbleck; runben; bennål; skaft; stämnyckel; kamskena; syllabarium; runes; runic inscription; runic object; U AST1;166; U Fv1983;229; U Fv1990;33; U Fv1990;37; U Fv1992;161C; U NOR2000;27A; U NOR2000;29; U NOR2001;19; Sl 3; Sl 9; Sl 14; Sl 17; Sl 28; Sl 76; Sl 82; Sigtuna lösföremål; Archaeology; Arkeologi; History and Archaeology; Historia och arkeologi